Faktor Penghambat Analisis Kebijakan Alokasi Dana Desa dalam Menunjang Pembangunan di Desa Sungai Baung Kecamatan Rengat Barat Kabupaten Indragiri Hulu - Andini, Maya; Malau, Hasbullah (PUBLICNESS: Journal of Public Administration Studies, 2023)
This study intends to determine the inhibiting factors of village fund allocation policy analysis in supporting development in Sungai Baung Village, West Rengat District, Indragiri Hulu Regency. The research was carried out utilizing a qualitative approach with a descriptive method. The research location was carried out in Sungai Baung Village, West Rengat District, Indragiri Hulu Regency. Researchers use purposive sampling methods and techniques. In this study using data types, namely primary data and secondary data. Data collection techniques are carried out by interviews, observation, and documentation. To ensure the accuracy of the data, the researchers employed triangulation techniques as a means of validating the information. In terms of analyzing the data, they employed techniques such as data reduction, data presentation, and drawing conclusions from the findings. The results showed that the analysis of the allocation of village funds in supporting development in Sungai Baung village, West Rengat District, Indragiri Hulu Regency was based on Indragiri Hulu Regent Regulation Number 42 of 2020 which in the budgeting process through planning, implementation, administration, reporting and accountability procedures. The allocation of village funds has adhered to the technical guidelines stipulated in laws and regulations; however, there is still room for improvement in its implementation to achieve optimal results. This is due to factors that affect the allocationn of village fundss in supporting development in Sungai Baung village, West Rengat District, Indragiri Hulu Regency, namely public ignorance of the village fund allocation for development andinsufficient land for the development of Sungai Baung village.